TPACK Model and digital competencies: Impact on teaching practice in ecuadorian school contexts - León Naranjo, Javier Rubén (2025)
The general objective of this study was to demonstrate the effect of the TPACK model on the development of digital skills among teachers at a private school in the Daule canton of Ecuador, during 2024. The research used a quantitative approach, with a quasi-experimental pretest-posttest design with control and experimental groups. The population consisted of 128 teachers, from which a non-probabilistic sample of 70 participants was chosen, equally divided into two groups. For data collection, a verified questionnaire was used that reviewed three aspects of digital skills: instrumental, didactic, and communicative. The results showed that, after implementing a program to improve digital skills based on TPACK, the experimental group showed significant improvements in all areas of living. 91.43% of the teachers in the experimental group reached a high level of digital skills, compared to only 25.71% of the control group. A significant increase was also noted in the instrumental, didactic, and communicative areas, demonstrating improved use, reflection, and education with technology. It was concluded that using the TPACK model has a positive impact on the overall growth of teachers' digital skills, helping them better integrate technological tools with lessons. These data support the idea that it is beneficial to include the model in ongoing courses for teachers; courses that seek to address the needs of today's education environment.